The molecular biology of Huntington's disease - Rubinsztein, David C. (Henry Stewart Talks, 2007)
Clinical presentations of HD, Pathological features, Genetic basis, Trinucleotide repeat expansion mutation, Huntingtin protein and cell damage, Abnormal protein aggregation, Transcriptional abnormalities, Raised levels of reactive oxygen species, Future directions for therapeutic intervention, siRNA approaches, Induction of autophagy, Update interview: Clinical presentations of HD, Update interview: Pathological features, Update interview: Genetic basis, Update interview: Trinucleotide repeat expansion mutation, Update interview: Future directions for therapeutic intervention, Update interview: RNAi approaches, Update interview: Induction of autophagy
Updated at 2020/05/22